weijoybase

8 Reputation

2 Badges

17 years, 74 days

MaplePrimes Activity


These are replies submitted by weijoybase

Thank you. I'm a matlab user, and not familiar with Maple. However, I'm very interested in Maple. Thank you for your help. I will try to use maple to solve problems.
Thank you. I'm a matlab user, and not familiar with Maple. However, I'm very interested in Maple. Thank you for your help. I will try to use maple to solve problems.
Thank you for your help. However,it does't work as i want. I want to solve e[0], e[1], e[2], e[3] from the equations. Here are the codes: restart; eq1 := e[0]^2+e[1]^2+e[2]^2+e[3]^2 = 1; A := Matrix([[e[0]^(2)+e[1]^2-1/2, e[1]*e[2]-e[0]*e[3], e[1]*e[3]+e[0]*e[2]], [e[1]*e[2]+e[0]*e[3], e[0]^(2)+e[2]^2-1/2, e[2]*e[3]-e[0]*e[1]], [e[1]*e[3]-e[0]*e[2], e[2]*e[3]+e[0]*e[1], e[0]^(2)+e[3]^2-1/2]]); A := evalm(2*A); vectorA := Matrix([a[1, 1], a[1, 2], a[1, 3]]); vectorB := Matrix([[b[1, 1]], [b[1, 2]], [b[1, 3]]]); eq2 := evalm(vectorA&*A&*vectorB)) = 0; vectorC := Matrix*(1, 4, symbol = c); vectorE := Matrix([[e[0]], [e[1]], [e[2]], [e[3]]]); eq3 := evalm(vectorC&*vectorE) = C; eq4 := e[0]+e[1]+e[2]+e[3] = 0; solve({eq4, eq3, eq1, eq2}, [e[0], e[1], e[2], e[3]]); It seems does't work. How can I solve the equation like this? Thank you very much.
Thank you for your help. However,it does't work as i want. I want to solve e[0], e[1], e[2], e[3] from the equations. Here are the codes: restart; eq1 := e[0]^2+e[1]^2+e[2]^2+e[3]^2 = 1; A := Matrix([[e[0]^(2)+e[1]^2-1/2, e[1]*e[2]-e[0]*e[3], e[1]*e[3]+e[0]*e[2]], [e[1]*e[2]+e[0]*e[3], e[0]^(2)+e[2]^2-1/2, e[2]*e[3]-e[0]*e[1]], [e[1]*e[3]-e[0]*e[2], e[2]*e[3]+e[0]*e[1], e[0]^(2)+e[3]^2-1/2]]); A := evalm(2*A); vectorA := Matrix([a[1, 1], a[1, 2], a[1, 3]]); vectorB := Matrix([[b[1, 1]], [b[1, 2]], [b[1, 3]]]); eq2 := evalm(vectorA&*A&*vectorB)) = 0; vectorC := Matrix*(1, 4, symbol = c); vectorE := Matrix([[e[0]], [e[1]], [e[2]], [e[3]]]); eq3 := evalm(vectorC&*vectorE) = C; eq4 := e[0]+e[1]+e[2]+e[3] = 0; solve({eq4, eq3, eq1, eq2}, [e[0], e[1], e[2], e[3]]); It seems does't work. How can I solve the equation like this? Thank you very much.
Page 1 of 1